The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A143555 G.f. satisfies: A(x) = 1 + x*A(x)^2/A(-x)^2. 5
 1, 1, 4, 8, 28, 80, 308, 984, 3980, 13472, 56164, 197032, 838396, 3013872, 13015188, 47624568, 207971436, 771336512, 3397886660, 12736715592, 56502898140, 213618833808, 953139545076, 3629043226392, 16270547827020, 62317467147744 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,3 COMMENTS Specific values:  A(2/9) = 17/9  and  A(-2/9) = 17/18. Radius of convergence: r = sqrt(2*sqrt(3)-3)/3 = 0.2270833462... with A(r) = (2 + sqrt(1-3*r))*(1+r^2)/(1+r) = 2.19775350... and A(-r) = (2 - sqrt(1+3*r))*(1+r^2)/(1-r) = 3*(1+r^2) - A(r) = 0.9569470... At x=r, the equation (*) (1+x^2)^2 - 2*(1+x^2)*y + (1+x)*y^2 - x*y^3 = 0, which is satisfied by y = A(x), factors out to:  (y - A(r))^2 * (y - A(r)*(1+r^2)/(2*(A(r)-1-r^2))) = 0; this gives the relation: (A(r)-1-r^2)*(3+3*r^2-A(r)) = r*A(r)^2.  At x>r, the equation (*) admits complex solutions for y. LINKS FORMULA G.f. satisfies: (1+x^2)^2 - 2*(1+x^2)*A(x) + (1+x)*A(x)^2 - x*A(x)^3 = 0. G.f. satisfies: A(x) = 1 + x*A(x)^2 + x^2 + x^2*A(-x). G.f. satisfies: A(x) = 1 + x^2 + x*A(x)^2/A(-x). G.f. satisfies: A(x) = 1 + x^2/(1 - A(-x)). G.f. satisfies: A(x) = 1 + ( 1 - (1+x^2)/A(x) )^2/x. G.f.: A(x) = (1+x^2)*G(x) where G(x) = 1 + x*G(x)^2/G(-x) is the g.f. of A143339. Recurrence: (n-1)*(n+1)*(4*n^3 - 32*n^2 + 71*n - 30)*a(n) = 6*(8*n^3 - 56*n^2 + 101*n - 10)*a(n-1) + 6*(12*n^5 - 132*n^4 + 499*n^3 - 700*n^2 + 102*n + 305)*a(n-2) - 18*(n-4)*(8*n - 25)*a(n-3) + 27*(n-5)*(n-4)*(4*n^3 - 20*n^2 + 19*n + 13)*a(n-4). - Vaclav Kotesovec, Dec 29 2013 a(n) ~ c * 3^(n-1) * 2*sqrt(6*sqrt(3)-6 + sqrt(9+6*sqrt(3))) / (2*sqrt(Pi) * (2*sqrt(3)-3)^(n/2+1/4) * n^(3/2)), where c = 4/(2+12^(1/4)) if n is even and c = 12/(6+12^(3/4)) if n is odd. - Vaclav Kotesovec, Dec 29 2013 EXAMPLE G.f. A(x) = 1 + x + 4*x^2 + 8*x^3 + 28*x^4 + 80*x^5 + 308*x^6 +... A(x)/A(-x) = 1 + 2*x + 2*x^2 + 10*x^3 + 18*x^4 + 98*x^5 + 210*x^6 +... where 1 - (1+x^2)/A(x) = x*A(x)/A(-x). Related expansions: A(x)^2/A(-x)^2 = 1 + 4*x + 8*x^2 + 28*x^3 + 80*x^4 + 308*x^5 +... A(x)^2 = 1 + 2*x + 9*x^2 + 24*x^3 + 88*x^4 + 280*x^5 + 1064*x^6 +... where A(x)^2/A(-x)^2 = A(x)^2 + x + x*A(-x). PROG (PARI) {a(n)=local(A=1+x*O(x^n)); for(i=0, n, A=1+x*A^2/subst(A^2, x, -x)); polcoeff(A, n)} CROSSREFS Cf. A143339, A143554, A143556, A143557, A143558, A143559. Sequence in context: A059480 A105723 A280118 * A025234 A075308 A300461 Adjacent sequences:  A143552 A143553 A143554 * A143556 A143557 A143558 KEYWORD nonn AUTHOR Paul D. Hanna, Aug 24 2008 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified August 4 20:00 EDT 2020. Contains 336202 sequences. (Running on oeis4.)